Manevi zararı tazmin yolları - Kazan, Hülya Atlan (My University, 2015)
Manevi zararın tazmin edilme biçimleri, doktrinde olduğu gibi, uygulamada da kapsama ilişkin sorulara ayrıntılı cevapların alınamadığı bir konudur. Manevi zarar esas olarak, parayla ve para dışında belirlenecek bir yöntemle tazmin edilir. Manevi tazminatın para biçiminde belirlenmesi halinde, hükmedilecek miktara esas alınacak belli başlı kriterlerin açık olmaması, bu konuda kanunun hâkime geniş bir takdir yetkisi vermiş olmasına dayandırılabilir. Ne var ki, hukuk güvenliği ile eşitlik ilkesinin gereği gibi uygulanmasını sağlamak, manevi tazminat miktarının belirlenmesinde göz önünde bulundurulacak kriterlerin (en azından her olayda uygulanabilecek asgari birtakım kriterlerin) tespit edilmesini gerektirir. Aynı amaçla, para dışında hangi yöntemlerin manevi zararı giderme amacını yerine getirebileceğinin (sınırlı sayıda bir tespit olmamakla birlikte) çerçevesi çizilmelidir. Tez çalışmamızda her iki manevi tazmin türünün kapsamına ilişkin belirsizlikler aydınlatılmaya çalışılmıştır. Tezin ilk bölümünde, kişiliğin korunmasının, manevi zarar ve manevi tazminat kavramlarının içeriği belirlenmiştir. İkinci bölümde, para biçiminde hükmedilen manevi tazminatın nesnel olarak belirlenebilmesine ilişkin yöntem ve önerilere yer verilmiştir. Para dışında hükmedilebilecek manevi tazminat türleri de son bölümde inceleme konusu yapılmıştır. Manevi zarar, manevi tazminat, manevi tazminatın hesaplanması, hesaplama yöntemleri, hesaplama çizelgeleri, tazminatın belirleneceği tarih, manevi tazminatın takdiri, para dışında hükmedilebilecek manevi tazminat türleri

Means of compensation for non-pecuniary loss is an issue for which detailed answers of questions regarding coverage cannot be received in practice just like in doctrine.Non-pecuniary loss, mainly, are compensated by money and by a method to be determined except money.If the non-pecuniary damage is determined by means of money, lack of clearance regarding certain criteria for the amount on which judging will be based, can be attributed to the fact that the law has granted a broad discretion to judges in this regard. However, it is necessary to determine the criteria (at least some minimum criteria that can be applied in each case) to be taken into account in determining the amount of compensation for ensuring that legal certainty and principle of equality are implemented properly. For the same purpose, the framework as to which methods can fulfill the purpose of compensation for non-pecuniary other than money (although not identified in admission limits) must be determined.We tried to clarify ambiguities as to the purview of both types of non-pecuniary damage in our thesis.In the first section of the thesis, the content of protection of personality as well as the content of the concepts of non-pecuniary loss and non-pecuniary damage has been determined.In the second section, methods and suggestions as to determining objectively the compensation awarded in the form of money have been provided.Types of non-pecuniary damage that can be awarded except money have been discussed ​​in the last section of the thesis. Non-pecuniary loss, non-pecuniary damage, calculation of non-pecuniary damage, calculation methods, calculation tables, the date of assessment of the compensation, discretion of the compensation, type of compensations to be awarded except money
Keywords: Medeni hukuk; Tazminat hukuku